Global ikat roots and routes of a textile technique the David Paly collection. (The Historic Textile Research Foundation, 2023)
"Deceptively simple or fantastically intricate, ikat technique has been used for many centuries to create extravagant costumes and cloths of deep cultural meaning. The distinctively blurred, feathered or jagged patterns of ikat-dyed textiles are found across much of the world -- from Japan in the east to Central and South America in the west, with vast areas of South-east Asia, India, Central Asia and the Middle East in between. The traditional patterns still hold cultural relevance today in significant parts of the long-established ikat-weaving areas. Textile artists and fashion designers in many and varied countries have taken ikat in new directions, respecting traditional forms and palettes while creatively diverging from them. This is the first time all the different iterations of this textile have been comprehensively brought together in one volume, drawing from the wide-ranging collection of David Paly. It is a journey across the world through the lens of ikat"--Provided by publisher.